2011
DOI: 10.1007/s10344-011-0573-3
|View full text |Cite
|
Sign up to set email alerts
|

Low survival after release into the wild: assessing “the burden of captivity” on Mallard physiology and behaviour

Abstract: Captive-reared animals used in reinforcement programs are generally less likely to survive than wild conspecifics. Digestion efficiency and naive behaviour are two likely reasons for this pattern. The Mallard is a species with high adaptability to its environment and in which massive reinforcement programs are carried out. We studied physiological and behavioural factors potentially affecting body condition and survival of captive-reared Mallards after being released. Digestive system morphology and an index o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 63 publications
2
60
1
Order By: Relevance
“…Our findings lend further support to the value of the SMI as a condition index (see also Peig and Green 2010;Bók-ony et al 2012;Champagnon et al 2012), and the relationship between SMI at ringing and at recapture was tighter than when relating crude body mass measurements. Future work relating the changes in individual body condition over time to reproductive success and survival in ducks, as well as in a range of other species, is highly desirable to allow us to better understand the relationships between body condition and individual fitness.…”
Section: Body Conditionsupporting
confidence: 67%
“…Our findings lend further support to the value of the SMI as a condition index (see also Peig and Green 2010;Bók-ony et al 2012;Champagnon et al 2012), and the relationship between SMI at ringing and at recapture was tighter than when relating crude body mass measurements. Future work relating the changes in individual body condition over time to reproductive success and survival in ducks, as well as in a range of other species, is highly desirable to allow us to better understand the relationships between body condition and individual fitness.…”
Section: Body Conditionsupporting
confidence: 67%
“…The rate of introgression due to genetic admixture is likely low due to the poor survival of released farmed mallards (Champagnon et al 2012b) but, as suggested by this study, restocking practice involves so many birds that the Bfootprintî n the wild population may be detectable and potentially significant. With continued releases, the genetic load of farmed stocks among wild mallards will persist or grow, potentially leading to lower fitness in the latter due to introgression of genotypes that are inferior under natural selection regimes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a change in genetic structure over time in farmed mallards is consistent with Lynch and O'Hely (2001), who argued that adaptation to captivity together with anthropogenic selection at breeding facilities will inevitably lead to a genetic alteration of the captive population. Such differences in genetics may, at least partly, explain discrepancies documented in captive ducks regarding morphology, e.g., brain volume (Guay and Iwaniuk 2008), digestive organs (Champagnon et al 2012b;Moore and Battley 2006), feeding apparatus Söderquist et al 2014), sexual behavior (Desforges and Wood-Gush 1976), mate preferences (Cheng et al 1978;Cheng et al 1979), and habituation to humans (Desforges and Wood-Gush 1975).…”
Section: Genetic Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Differences in the morphology of digestive organs between captive and wild birds have often been reported as a cause and consequence of inappropriate diet leading to bird weakness or death Communicated by M. Scandura (Champagnon et al 2011;Moore and Battley 2006;Putaala and Hissa 1995). Due to the absence of parental learning, captive-bred individuals might express feeding preferences for particular food colour, shape or texture close to the food distributed in captivity (food "imprinting"), but with no or low nutritional value (Barker et al 1977).…”
Section: Introductionmentioning
confidence: 98%